Use of natural brine and minerals as non-root nutrition on agricultural crops - Pysarenko, P.; Samoilik, M.; Dychenko, O.; Lastovka, V.; Husynskyi, D.; Shpуrna, V.; Zhilin, O. (Scientific Progress & Innovations, 2025)
Today, when drawing up zonal farming systems, special attention should be paid to the use of local raw materials in order to increase the effective fertility of the soil and biologize agriculture, in particular natural brines and minerals. The main purpose of this work is to determine the possibilities of using natural brines and minerals as foliar top dressing for crops.As a result of the conducted research, it was found that the use of mineralized aquifer water (AWW) for fertilizing winter wheat is effective both in the tuberization phase and in the earing phase. However, the use of AWW in the tuberization phase is more appropriate, because in this phase winter wheat spends the most energy on combating weeds that clog it, and therefore the herbicidal effect of AWW allows you to destroy wintering weeds, such as field talaban, common buckwheat and others, and the introduction of nutrients has a positive effect on plant productivity. In particular, when using different AWW norms in the tuberization phase, the maximum yield increase was 5.2 c/ha (16.6 %), and when using it in the earing phase – 4.2 c/ha (13.5 %). Mineralized aquifer water allows not only to create certain conditions for regulating the nutrient regime of the soil, due to the influx of both inorganic and organic chemistry elements, optimization of microbiological and enzymatic activity of the soil, but also to effectively control the contamination of winter wheat crops with weeds. According to the results of physicochemical analyses of the soil sample, it was found that when using mineralized aquifer water in the soil solution, the content of nitrates not only does not increase, but even decreases, although they are part of it. This can be explained by the fact that MPW stimulates the growth and development of not only plants, but also soil biota, which is a direct consumer of anions and cations. It is substantiated that mineralized formation water allows to obtain yield increases at an application rate of 500–1000 l/ha, both due to the influence of the organic and inorganic part (35.5 and 35.9 c/ha, respectively, which is 4.4–4.8 c/ha more than the control). An increase in yield when using bischofite is observed at an application rate of 100–300 l/ha (33.2 c/ha and 34.5 c/ha, which is 2.0–3.3 c/ha higher than the control). Although the use of mineralized formation water leads to a higher yield increase than bischofite, the application of bischofite solution corresponds to the technological capacity of the unit.